2022
DOI: 10.3389/feduc.2022.896833
|View full text |Cite
|
Sign up to set email alerts
|

Cultural resources, academic self-concept, and achievement of chemistry students in senior secondary schools of Calabar Municipality, Cross River State, Nigeria

Abstract: This paper investigated cultural resources, academic self-concept, and achievement of chemistry students in a senior secondary school in Nigeria. Research questions and hypotheses were formulated to direct the study. A quasi-experimental factorial design was used in this study, which had a sample size of 90 senior secondary chemistry students. The Academic Self-concept Questionnaire (ASCQ) and Chemistry Achievement Test (CAT) were used in this study. The reliability of ASCQ was done using Cronbach Alpha and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The general performance of students in Chemistry WAEC examinations from 2013 to 2018 at the national level indicated that the performance of students ranges from 58% to 63% credit pass (Nja et al, 2022a). This showed that students have not been doing well in chemistry examination in WAEC as there was no year that students score up to 70% in the years under review.…”
Section: Introductionmentioning
confidence: 99%
“…The general performance of students in Chemistry WAEC examinations from 2013 to 2018 at the national level indicated that the performance of students ranges from 58% to 63% credit pass (Nja et al, 2022a). This showed that students have not been doing well in chemistry examination in WAEC as there was no year that students score up to 70% in the years under review.…”
Section: Introductionmentioning
confidence: 99%
“…This seating arrangement is vital when educators seek to facilitate active learning environment particularly in a blended learning classroom (Clinton & Wilson, 2019;Ochola & Achrazoglou, 2015; Serrano, Dea-Ayuela, Gonzalez-Burgos, Serrano-Gil, & Lalatsa, 2019). Many researches have indicated that active learning contributed to a greater extent high academic achievement of students (Idiege, Nja, & James, 2021;Mello & Less, 2013;Momani, Asiri, & Alatawi, 2016;Nja et al, 2022a). Active students' engagement is paramount in the teaching of science education courses as it enhances students' interest in the course which in turn leads to improved learning outcomes (Nja & Ideba, 2021;Nja, Ukwetang, Orim, Cornelius-Ukpepi, & Ndifon, 2022b;Reinke, 2019).…”
Section: Introductionmentioning
confidence: 99%